The role of conformational motions in the control of ligand binding to myoglobin and hemoglobin - Philipp, Robert Georg (1994)
Restriction data tranferred 2014-07-01T11:23:44-05:00 Original Data Group with Access UIUC Users [automated] Release Date: none Reason: ETDs are only available to UIUC Users without author permission ETDs are only available to UIUC Users without author permission U of I Only Myoglobin and hemoglobin are dioxygen storage and transport proteins. They bind small molecules (ligands) such as dioxygen (O$\sb2$) and carbon monoxide (CO) reversibly. The active site is the heme, a disc shaped molecule which sits in a pocket of the protein (heme pocket). At the center of the heme is an iron (Fe) atom, to which the ligands bind reversibly when the Fe is in the ferrous state. The ligand binding rates of these proteins depend on the type of ligand. For example, myoglobin and hemoglobin bind O$\sb2$ faster, but with lower affinity, than they bind CO. The mechanism with which these proteins control ligand binding is not fully known, and remains a fundamental issue, if the general principles of ligand binding are to be understood. Protein motions are essential for myoglobin and hemoglobin to perform their function. X-ray crystal structures show no pathways through which the ligands can enter and exit the protein. Without the ability of ligand entry and exit, myoglobin and hemoglobin could not deliver O$\sb2$ to the required tissues. Large scale motions are required to open pathways for ligand entry and exit. Additional motions have been shown to be important for control of the ligand binding barrier. The bound and deoxy structures of myoglobin and hemoglobin are different, respectively. One important difference is the position of the heme-iron relative to the heme plane. Upon ligand dissociation, the Fe relaxes to its unbound position. Movement of the Fe out of the mean heme-plane has been correlated to the height of the rebinding enthalpy barrier. We have conducted flash photolysis experiments on R and T state carp hemoglobin and sperm whale myoglobin over a wide range in temperature (10K to 300K) and time (30ns to ...